Synthetic Peptide Libraries: From Random Mixtures to In Vivo Testing - Sandomenico, Annamaria; Caporale, Andrea; Doti, Nunzianna; Cross, Simon; Cruciani, Gabriele; Chambery, Angela; De Falco, Sandro; Ruvo, Menotti (Current Medicinal Chemistry, 2020)
Combinatorially generated molecular repertoires have been largely used to identify novel bioactive compounds. Ever more sophisticated technological solutions have been proposed to simplify and speed up such process, expanding the chemical diversity space and increasing the prospect to select new molecular entities with specific and potent activities against targets of therapeutic relevance. In this context, random mixtures of oligomeric peptides were originally used and since 25 years they represent a continuous source of bioactive molecules with potencies ranging from the sub-nM to microM concentration. Synthetic peptide libraries are still employed as starting “synthetic broths” of structurally and chemically diversified molecular fragments from which lead compounds can be extracted and further modified. Thousands of studies have been reported describing the application of combinatorial mixtures of synthetic peptides with different complexity and engrafted on diverse structural scaffolds for the identification of new compounds which have been further developed and also tested in in vivo models of relevant diseases. We briefly review some of the most used methodologies for library preparation and screening and the most recent case studies appeared in the literature where compounds have reached at least in vivo testing in animal or similar models. Recent technological advancements in biotechnology, engineering and computer science have suggested new options to facilitate the discovery of new bioactive peptides. In this instance, we anticipate here a new approach for the design of simple but focused tripeptide libraries against druggable cavities of therapeutic targets and its complementation with existing approaches.
Keywords: in vivo testing